2015
DOI: 10.1016/j.biomaterials.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the osteoinductive potential of a bio-inspired scaffold mimicking the osteogenic niche for bone augmentation

Abstract: Augmentation of regenerative osteogenesis represents a premier clinical need, as hundreds of thousands of patients are left with insufficient healing of bony defects related to a host of insults ranging from congenital abnormalities to traumatic injury to surgically-induced deficits. A synthetic material that closely mimics the composition and structure of the human osteogenic niche represents great potential to successfully address this high demand. In this study, a magnesium-doped hydroxyapatite/type I colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
161
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(172 citation statements)
references
References 59 publications
11
161
0
Order By: Relevance
“…49,50 Hence, we provided a new method for biomimetic mineralization based on the PILP strategy, in which collagen gels after self-assembly, but not dry collagen scaffolds, were immersed into the CMC/ ACP nanocomplex solution. Compared with the direct mixing of collagen solution and mineral ions 11,46,47 or immersing the dry collagen scaffolds in the mineral solution, 13,23,51 the mineralized method described in this study can cause the collagen scaffold to have a water oversaturated status after self-assembly. This status may make the nanocomplexes of CMC/ACP more easily intercalate into the interstices of the collagen fibrils, which is the crux of intrafibrillar mineralization of collagen scaffolds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…49,50 Hence, we provided a new method for biomimetic mineralization based on the PILP strategy, in which collagen gels after self-assembly, but not dry collagen scaffolds, were immersed into the CMC/ ACP nanocomplex solution. Compared with the direct mixing of collagen solution and mineral ions 11,46,47 or immersing the dry collagen scaffolds in the mineral solution, 13,23,51 the mineralized method described in this study can cause the collagen scaffold to have a water oversaturated status after self-assembly. This status may make the nanocomplexes of CMC/ACP more easily intercalate into the interstices of the collagen fibrils, which is the crux of intrafibrillar mineralization of collagen scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Among these biomaterials, type 1 9 To date, mixing collagen with minerals and mineralizing collagen have been used to modify collagen scaffolds for simulating the composition and microstructure of bone tissue to the greatest extent possible. [10][11][12][13][14][15][16][17] Because HA is a primary mineral component of natural bone and possesses outstanding bioactivity, osteoconductivity, biocompatibility with bone cells, good mechanical properties, and a slow degradation rate in vivo, it has often been the first choice for modifying collagen scaffolds. 10,[18][19][20] Although directly mixing collagen with HA powders in certain proportions can result in collagen scaffolds with compositions similar to those of natural bone tissues, it is difficult to simulate their microstructure and microenvironment via this process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the magnesium-doped hydroxyapatite/ collagen scaffold mimicking the hypoxic condition in the osteogenic niche might be responsible for maintaining the cells in a quiescent state. 9,39 On the other hand, ion-induced cell death such as that from excessive Ca 2+ may account for lower cell viability resulting from the initial ion release from the composite scaffolds. 40,41 Collagen-based materials that serve as analogs of organic components of bone matrix have previously been developed for bone regeneration.…”
Section: Yu Et Almentioning
confidence: 99%
“…6,7 The hydroxyapatite/collagen composite scaffolds mimicking the structure and composition of trabecular bone were extensively investigated, and they have been shown to have great potential in bone repair and regeneration. [8][9][10] The hydroxyapatite-collagen pairing naturally occurs in bone, whereby the collagen matrix provides strength and structural stability, whereas hydroxyapatite reinforces the organic matrix. 11 The organic matrix containing collagen and noncollagenous proteins plays an important role in mineralization, during which the organic matrix not only directs mineral deposition but also guides its growth.…”
mentioning
confidence: 99%